The role of ultrasonic guided fine needle aspiration cytology in the diagnoses of renal masses - Abid, Ali Hussein; Mohammad, Ehab Jasim; Alani, Mohammed Kamal Rasheed (International Surgery Journal, 2017)
Background: FNAC has been widely applied in the diagnosis of tumors and tumor like lesion of the abdomen including the kidney. The aim of this study was to evaluate the outcome of FNAC to a sample of Iraqi patients with kidney tumor. Methods: Patients with clinical, radiological suspicion of renal masses underwent FNAC of the kidney under ultrasound guidance were invited to this study. Those who fulfilled inclusion criteria were recruited. FNAC was done in accordance with stipulated clinical practice. Results: 53 patients with clinical and radiological suspicion of renal mass underwent FNAC of the kidney under ultrasound guidance. The age ranged from 1-2 year to 70 years (mean 44.7 years) with male to female ratio (1.9:1). Around 94.3% had primary renal mass, 1.9% metastatic tumor to the kidney and the rest 3.8% was undiagnosed. Sensitivity was 90% while specificity was 100%. Conclusions: We conclude that FNAC of the renal masses is safe and reliable, and fast diagnostic procedure in the evaluation of patient with renal masses.